Left Renal Vein Stenting in Nutcracker Syndrome: Outcomes and Implications - Patrick Cherfan (Vascular and Endovascular Review, 2020)
Nutcracker syndrome refers to the symptomatic extrinsic compression of the left renal vein presenting most commonly as flank pain and haematuria. While surgery remains the first-line treatment, stenting is gaining more acceptance and there are now several published case series. This article highlights the outcomes of left renal vein stenting in the setting of nutcracker syndrome.